Effect of Mixing on the Density and Chlorophyll A Content on Botryococcus Sp. - Harun, Mazhatarmizi; Matias Peralta, Hazel Monica; Gonawan, Nurul Huda; Shahri, Zarina (Journal of Science and Technology, 2018)
Optimization of the growth of microalgae is essential due to demand for high biomass yields. In addition, the methods to estimate the growth (as cell density or biomass) of microalgae are tedious. The normal methods include cell counts, optical density, chlorophyll a and ash free dry weight. However, at least two of these methods were done together for every growth experiment to get a better result. Therefore, this study investigates the effect of mixing as one of the many factors that determines the growth of microalgae, Botryococcus sp. In addition, three different methods to estimate the growth (in terms of cell density or biomass) will be utilized. Three different treatments on the effect of mixing were employed (T1 using aeration; T2 manual hand shake two times daily; T3 no aeration and shaking) for these experiments. The experiment was carried out under outdoor conditions with temperature ranging from 25.8°C to 35.5°C, light intensity from from 200 Lux to 18000 Lux and pH of 7 to 8 units for 24 days using Bold basal medium (BBM) as growth media. Microalgae biomass was estimated by optical density, chlorophyll a and cell count using haemocytometer. The highest density of Botryococcus sp. was achieved (10.74 x 106 cell ml-1day-1; OD of 3.246 at 680nm; 0.7843 mg L-1day-1 chlorophyll a) with aeration. Whereas, the lowest (2.78 x 106 cell ml-1day-1; od 1.007 (680nm); chlorophyll a 0.1586 mg L-1day-1) and (3.07 x 106 cell ml-1day-1; od 0.999 (680nm); chlorophyll a 0.1545 mg L-1day-1) with shaking and no aeration, respectively. There exist a positive linear relationship between cell counting and optical density (R2=0.96); cell count and chlorophyll a (R2=0.95); and optical density and chlorophyll a (R2= 0.98) were observed. The result of this study suggested that constant aeration is required by the microalgae, Botryococcus sp. for growth in terms of cell density and biomass.